Tobacco plants (Nicotiana benthamiana) were influenced by silicon and were not infected by dodder (Cuscuta europaea) - Lukacova, Zuzana (Plant physiology and biochemistry : PPB, 2019)
Copyright © 2019 Elsevier Masson SAS. All rights reserved.